Effect of exercise on bone mineral density among patients with osteoporosis and osteopenia: A systematic review and network meta‐analysis. Issue 15 (1st November 2021) - Zhang, Shifang; Huang, Xiuxiu; Zhao, Xiaoyan; Li, Bei; Cai, Ying; Liang, Xiaoqin; Wan, Qiaoqin
Abstract: Aims and objectives: To systematically review and compare the efficacy of different exercise interventions on bone mineral density (BMD, g/cm 2 ) in patients with osteoporosis and osteopenia. Background: It is vitally important to prevent and treat bone loss in patients with osteoporosis and osteopenia. Exercise can effectively increase bone density and slow down bone loss in middle‐aged and older people. However, it is still unclear which type of exercise intervention is the most effective on bone mineral density. Design: Systematic review and network meta‐analysis (NMA) according to PRISMA. Methods: Randomised controlled trials of different exercise treatments for osteopenia and primary osteoporosis were included. A Frequentist network meta‐analysis was conducted to appraise the efficacy of different types of exercise. The outcome was bone mineral density of different parts of the body. Results: Ninety‐seven studies were included. The network meta‐analysis showed that combined exercise, resistance exercise, aerobic exercise and mind‐body exercise had a significant effect in improving the bone density of lumbar spine. The surface under the cumulative ranking area (SUCRA) values for mind‐body exercise was 0.99 and ranked first. For BMD of the femoral neck, all kinds of exercise interventions increased the bone density significantly compared with no exercise and the optimal type was mind‐body exercise (SUCRA = 0.99). In terms of the total hip bone mineral density, aerobic exercise and resistance exercise could improve hip bone density, with the resistance exercise (SUCRA = 0.95) ranking as first. Conclusions: This NMA demonstrated the mind–body exercise might be the optimal exercise type to increase the BMD of the lumbar spine and femoral neck and resistance exercise is the most promising type for total hip BMD.